Polycyclic aromatic hydrocarbons bound to outdoor and indoor airborne particles (PM2.5) and their mutagenicity and carcinogenicity in Silesian kindergartens, Poland - Błaszczyk, Ewa (Air Qual Atmos Health, 2016)
Assessment of exposure to polycyclic aromatic hydrocarbons (PAHs) is important due to the widespread presence of PAHs in the environment and their toxicological relevance, especially to susceptible populations such as children and their health. The aim of this study is to compare indoor and outdoor concentrations of particulate matter with a diameter of 2.5 μm or less (PM2.5) and 15 individual PAHs, as well as contribution of the analyzed PAHs to mutagenic and carcinogenic activity. Samples were collected during spring season in two sites in southern Poland (Silesia) representing urban and rural areas. Indoor samples of PM2.5 were sampled in kindergartens. At the same time, in the vicinity of the kindergarten buildings, the collection of the outdoor PM2.5 samples was carried out. Mutagenic (MEQ) and carcinogenic (TEQ) equivalents related to BaP and the percentage share expressed as mutagenic (MP) and carcinogenic (CP) potential of each individual compound to the total mutagenic/carcinogenic potential of the PAH mixture were calculated. The obtained results show that high concentrations of PM2.5 (above 25 μg/m(3)) and 15 PM2.5-bound PAHs in outdoor and indoor air were similar in the two studied areas. In overall PAHs mutagenic and carcinogenic potential, the percentage share of benzo(a)pyrene (BaP) was dominant and varied from 49.0–54.5% to 62.5–70.0%, respectively. The carried out study indicates the necessity of reducing PAH emission from solid fuel combustion, which is reflected in PM2.5-bound PAHs concentrations and their diagnostic ratios. In the recent years, health effects on children resulting from their activity pattern and air quality in the public places have been a serious problem.